2018
DOI: 10.1016/j.jaci.2017.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent stem cell models of Blau syndrome reveal an IFN-γ–dependent inflammatory response in macrophages

Abstract: Our data support the significance of ligand-independent autoinflammation in the pathophysiology of Blau syndrome. Our comprehensive isogenic disease-specific iPSC panel provides a useful platform for probing therapeutic and diagnostic clues for the treatment of patients with Blau syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 40 publications
8
39
0
Order By: Relevance
“…We previously demonstrated that such MLs can be used to model the proinflammatory phenotypes of various autoinflammatory disorders [14,[28][29][30]. Combined with the current study, which successfully identified candidate compounds, we concluded that this ML-based HTS system provides a versatile platform for screening candidate compounds for treating autoinflammatory disorders.…”
Section: Discussionsupporting
confidence: 64%
“…We previously demonstrated that such MLs can be used to model the proinflammatory phenotypes of various autoinflammatory disorders [14,[28][29][30]. Combined with the current study, which successfully identified candidate compounds, we concluded that this ML-based HTS system provides a versatile platform for screening candidate compounds for treating autoinflammatory disorders.…”
Section: Discussionsupporting
confidence: 64%
“…HASMCs were seeded onto multi-well glass-bottom dishes. The nuclear translocation of NF-κB p65 subunit was evaluated as previously described [ 14 ]. After culture for the indicated time periods, cells were fixed with 4% paraformaldehyde in PBS (−) for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…HASMCs were transfected with pGreenFire NF-κB transcription reporter lentivector (System Biosciences, Mountain View, CA) inserted with the Renilla gene under the CMV promoter as an internal control [ 14 ]. The NF-κB activity was then measured using the Dual-Luciferase Reporter Assay System (Promega, Madison, WI).…”
Section: Methodsmentioning
confidence: 99%
“…Tangier disease (mutations in ABCA1 ), lysosomal storage diseases including neuronal ceroid lipofuscinoses (NCLs) 27 and Gaucher disease (GD, mutations in GBA ), 28, 29 chronic granulomatous disease (CGD, defective NADPH oxidase), 30 Blau syndrome (mutation in NOD2 ), 31 and chronic infantile neurologic cutaneous and articular syndrome (CINCA syndrome, mutation in NLRP3 ). 32 Some of these studies compared the phenotypes of IPSDM and HMDM derived from the same subjects 8, 29 to further validate the fidelity of IPSDM in assessing the functionality of genetic mutations.…”
Section: Disease Modeling and Functional Genomic Analyses With Ipsdmmentioning
confidence: 99%